Impact of Physical Rehabilitation Therapy on Improving Cardiovascular Health in Patients with Obesity - Angélica Irene López Asqui,; Jhonier Orlando Castro Trejo,; Marianela Bastías Pérez, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study analyzes the effects of physical rehabilitation therapy on the cardiovascular health of patients with obesity. Through an intervention that includes aerobic, resistance and flexibility exercises, improvements in cardiovascular risk factors, such as blood pressure, lipid profile and body mass index (BMI) are observed. It is concluded that physical rehabilitation contributes significantly to reducing these risk factors, improving cardiovascular health in obese patients.